Virulence frequencies of Xanthomonas oryzae pv. oryzae on different sets of rice differentials under Punjab agro-ecological zones - and JAGJEET SINGH LORE, MANDEEP SINGH HUNJAN*, PUSHPINDER PAUL SINGH (Indian Phytopathology, 2014)
Virulence frequencies on a particular differential were calculated as the ratio of virulent isolates of Xanthomonas oryzae pv. oryzae to the number of total isolates tested. Numerical data pertaining to disease score (0-9) was analysed by virulence analysis tool. In this study, virulence frequencies to the resistance genes present in the standard international differentials including near isogenic lines (NILs) and local rice cultivars, ranged between 0–1 (representing zero to 100 per cent). None of the single gene was found to be effective against all the X. oryzae pv. oryzae isolates. Out of total 105 tested isolates, 73.2 percent were infective on Xa4 gene, 72.3 percent on xa5 gene and only 9 percent on xa13 gene. The combination of xa5 and xa13 (IRBB-53) was the most effective, on which none of the X. oryzae pv. oryzae isolates were found virulent. The data was also correlated with distribution of X. oryzae pv. oryzae virulences in different agro-ecological zones of Punjab. Among the local cultivars, the highest virulence frequency percentage was observed on cultivar PAU 201 (77.8%) in South and south-western districts of Patiala and Sangrur, while none was observed in western plain and northern regions of Punjab. This study shows the in effectiveness of single resistance genes, implying that only two or more gene combinations can manage bacterial blight disease effectively in Punjab.